The Utilization of Separate Elements of Vitagenic Technologies while Usingh Folk Proverbs, Sayings, Omens and Beliefs at Ukrainian Language Lessons - Olga Blazhevych (Pedagogical Discourse, 2013)
Based on scientific research of domestic and foreign scholars, educators, ethnographers and anthropologists, materials and pedagogical publications, own experience of the author, the article discovers hot issues regarding the application of certain elements of vitagenic technologies using folk proverbs, omens and beliefs during Ukrainian Language lessons conduction. The research makes emphasis on the forms of oral folklore, which show the diversity of life, the sphere of everyday life, reveal customs of our nation, its history and morality, stress that they are an invaluable treasure of folk wisdom which accompanied people from the ancient times to the present days.